Development and implementation of performance based salary system for sales force of Coca Cola Bangladesh - Koly, Farzana Rahman (BRAC Univeristy, 2018)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Masters of Business Administration, 2017.